Porcine NK cells display features associated with antigen-presenting cells. Issue 1 (21st December 2017) - De Pelsmaeker, Steffi; Devriendt, Bert; Leclercq, Georges; Favoreel, Herman W
Abstract: NK cells are members of the innate immunity and play a central role in the defense against viral infections and cancer development, but also contribute to triggering and shaping adaptive immune responses. Human NK cells may express MHC II and costimulatory molecules, including CD86, CD80, and OX40 ligand, which allows them to stimulate the CD4 + T-cell response. In contrast, murine NK cells do not express MHC II or costimulatory molecules. Upon activation, mouse NK cells can acquire these molecules from dendritic cells (DCs) via intercellular membrane transfer, which leads to suppression of DC-induced CD4 + T-cell responses rather than stimulation of T-cell responses. Previous studies showed that porcine NK cells can express MHC II molecules, but it was unknown if porcine NK cells also express costimulatory molecules and whether NK cells may affect T-cell proliferation. We found that primary porcine NK cells express functional MHC II molecules and costimulatory CD80/86, particularly upon activation with IL-2/IL-12/IL-18, and that they are able to stimulate T-cell proliferation. In addition, we show that porcine NK cells are able to internalize antigens derived from killed target cells in an actin polymerization-dependent process. All together, these results indicate that porcine NK cells possess properties associated with APCs, which allows them to stimulate T-cell proliferation.